Tantangan Implementasi Logistik Halal di Indonesia - Saribanon, Euis; Indriyati, Indriyati; Setiawan, Agus (Institut Transportasi dan Logistik Trisakti, 2023)
The purpose of this study is to analyze the opportunities and challenges that occur in the implementation of halal logistics in the logistics industry in Indonesia. In its implementation, there is still a lack of compatibility between realization and halal logistics goals. Halal logistics companies still have opportunities because the number of Muslims is large and the need for halal products is increasing. The method used begins with the steps in the form of literature studies, existing contitions and previous research studies, data collection with FGDs, identification of opportunities and challenges and the last stage is conducting studies or analysis to obtain strategies for developing innovation using PEST analysis from three logistics companies that have has carried out halal logistics and has a halal certificate. The results of this study show that the biggest challenge in implementing halal logistic is government regulation that is still incomplate and consistent and the adoption of technology by halal logistic perpetrators is uneven.